2017
DOI: 10.5534/wjmh.2017.35.2.100
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Impact of Voiding Posture on Uroflowmetry Parameters in Men

Abstract: PurposeTo evaluate the impact of voiding position on uroflowmetry parameters and to assess its potential clinical implications.Materials and MethodsWe conducted a prospective study from 2013 to 2015 and included men between 18 and 77 years old who were either healthy volunteers with an International Prostate Symptom Score (IPSS) ≤7 or men with benign prostate enlargement that were on alpha-blocker medication and had an IPSS <10. Participants underwent uroflowmetry and post-void residual urine (PVRU) measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
0
8
0
4
Order By: Relevance
“…Additionally, Goel et al (2017) conducted a study to evaluate the impact of voiding position on uroflowmetry parameters and PVRU on healthy volunteers and patients with BPH in different age groups. He reported that voiding in the sitting position was reported to be the optimal position for elderly men; however, the significant changes are there only on PVRU volume and voiding time (Goel et al, 2017). In contrast to the above mentioned studies, we found that almost all uroflowmetry parameters and PVRU volume in BPH patients showed statistically significant differences in favor of standing over sitting position.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Goel et al (2017) conducted a study to evaluate the impact of voiding position on uroflowmetry parameters and PVRU on healthy volunteers and patients with BPH in different age groups. He reported that voiding in the sitting position was reported to be the optimal position for elderly men; however, the significant changes are there only on PVRU volume and voiding time (Goel et al, 2017). In contrast to the above mentioned studies, we found that almost all uroflowmetry parameters and PVRU volume in BPH patients showed statistically significant differences in favor of standing over sitting position.…”
Section: Discussionmentioning
confidence: 99%
“…[2] İşeme pozisyonunun ürodinamik parametreleri etkileyerek işeme üzerine etkileri olabileceği düşünülmüş ve bu konuda sınırlı sayıda olsa da pek çok çalışma dizayn edilmiştir. [3][4][5][6] Yaşlanan erkek popülasyonunda ürolojik olan ve olmayan pek çok faktör alt üriner sistem semptomlarına (AÜSS) neden olabilir. Yaş ile birlikte mesanede ve nörolojik fonksiyonlarda değişiklikler meydana gelebilir.…”
Section: Sonuçunclassified
“…[10] İşeme pozisyonunun üroflowmetri parametreleri ve PVR üzerine etkisi konusunda sınırlı sayıda çalışmalar yapılmıştır. [3][4][5][6][10][11][12] Sağlıklı 66 genç erkekle yapılan ve işeme pozisyonunun üroflowmetri parametreleri ve PVR üzerine etkisini araştıran bir çalışmada oturur pozisyonda işemede ayakta ve çömelerek işemeye göre idrar akım hızının daha düşük olduğu ve işeme süresi daha uzun olduğu bulunmuştur. PVR değerleri ise her üç pozisyonda benzer olarak bulunmuştur (ayakta işeme sonrası PVR: 4,9±3,6 mL, oturarak işeme sonrası PVR: 6,4±6,7 mL, çömelerek işeme sonrası PVR: 5,3±4,5 mL, p>0,05).…”
Section: Sonuçunclassified
See 1 more Smart Citation
“…The voiding position plays an important role in the uro lowmetry parameters of elderly men. Voiding in the sitting position was found to be optimal for elderly men, whereas the role of the voiding position in healthy young men could not be determined" [47] (Figure 14).…”
Section: Treatment Of Overactive Bladder/interstitial Cystitismentioning
confidence: 99%